Associations between White Blood Cell Count and the Development of Incidental Nonalcoholic Fatty Liver Disease - Goh Eun Chung; Jeong Yoon Yim; Donghee Kim; Min-Sun Kwak; Jong In Yang; Su Jin Chung; Sun Young Yang; Joo Sung Kim (Gastroenterology Research and Practice)
Aims. Chronic low-grade inflammation is thought to be associated with the pathogenesis of nonalcoholic fatty liver disease (NAFLD). This study aimed to determine the association between serum white blood cell (WBC) counts and the development of incidental NAFLD. Methods. In this retrospective longitudinal cohort study, we recruited participants who underwent abdominal ultrasonography and blood samplings during medical checkups in both 2005 and 2010. A total of 2,216 subjects were included in our analyses. Results. The prevalence of NAFLD in 2010 increased steadily in conjunction with increasing WBC counts in 2005 after adjustment for body mass index (BMI) [odds ratio (OR) 2.44, 95% confidence interval (CI) = 1.49–4.00 for women and OR 2.42, 95% CI = 1.61–3.63 for men, lowest quartile versus highest quartile]. Multivariate regression analysis after adjusting for age, BMI, hypertension, smoking, triglycerides, HDL cholesterol, and glucose levels revealed that NAFLD was significantly associated with the highest WBC quartile compared to the lowest quartile [OR 1.85, 95% CI, 1.10−3.10 for women and OR 1.68, 95% CI, 1.08−2.61 for men]. Conclusions. We demonstrated that the risk of developing NAFLD was significantly associated with WBC counts independently of metabolic factors. This finding provides novel evidence indicating that serum WBC counts may be potential surrogate markers of NAFLD.